When men appear smaller or larger than they really are: preliminary evidence that women are fooled by size illusions in attractiveness judgment tasks - Ludwig, Yannick S.; Pollet, Thomas V. (Anthropological Review, 2014)
In humans, studies have shown that contrast illusions can affect perceptions of facial attractiveness and dominance. In non-human animals, recent research found that contrast illusions of size positively affected male mate value. In humans, male height is a potentially important indicator of mate value, with women preferring men taller than themselves. We tested in two studies whether height contrast illusions could affect women’s perceptions of male height and mate value, particularly attractiveness, dominance, and muscularity. Using computer-generated images of men of different heights standing in groups of three, 104 female participants rated targets either surrounded by shorter, same height, or taller distractors in a within-subject design. The second experiment (N=80) replicated and extended the first by making the images more realistic and adding natural backgrounds, suggesting that when participants are given a visual anchor, in order to get a better sense of the absolute height of the targets, the effects remain. In both studies, results showed that, compared with same height distractors, male targets were rated as taller when surrounded by shorter distractors, and as shorter when surrounded by taller distractors. Additionally, attractiveness, dominance, and muscularity perceptions were affected in a similar manner, with most of the differences in these appraisals being mediated by the perceived height differences. Therefore, differently sized distractors affected the perceived height and mate value of the targets, which were in effect all of the same constant size. These findings indicate that context dependent effects could potentially influence attractiveness judgments. The same man might thus be perceived as more attractive when surrounded by men of similar or smaller height, as opposed to when surrounded by men who are taller.